Emotion regulation among undergraduates in Malaysia: Distress tolerance, mindfulness, and positive reappraisal - Ching, Kai Xuan (2023)
This research aimed to determine the relationships between emotion regulation, distress tolerance, mindfulness, and positive reappraisal of undergraduates in Malaysia. This research has adopted a quantitative cross-sectional correlational research design, and data were collected through online surveys. A total of 218 samples were gathered through purposive sampling, which involved undergraduates in Malaysia whose age were between 19 years old and 26 years old (M = 21.234; SD = 1.276). Majority of the survey respondents were female (n = 141, 64.68%), followed by male (n = 77, 35.32%). The location of this research and data collection was primarily online platforms such as Instagram and WhatsApp, and University Tunku Abdul Rahman, Kampar campus. However, the participants included undergraduates from several states across Malaysia. Besides the informed consent and demographic information, the instruments that were included in the questionnaire were Difficulties in Emotion Regulation Scale-16 (DERS-16), Distress Tolerance Scale-Short Form (DTS-SF), Mindful Attention Awareness Scale (MAAS), and Positive Reappraisal Subscale. Based on the results, emotion regulation was significantly and positively related to distress tolerance, mindfulness, and positive reappraisal. It was also found out that distress tolerance and mindfulness were significant predictors for emotion regulation, while positive reappraisal was not. Therefore, the findings of this research would provide theoretical evidence for Mindfulness-to-Meaning Theory. Besides, the findings of this research would also provide practical benefits for the mental health care providers who could be dealing with clients with emotion regulation difficulties in their practices, as well as the undergraduates who need to improve their emotion regulation abilities.